2012
DOI: 10.1097/sla.0b013e318250b332
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Study on Avoidable Stressors and Countermeasures Affecting Surgical Motor Performance and Learning

Abstract: OBJECTIVE To explore how the two most important components of surgical performance - speed and accuracy - are influenced by different forms of stress and what the impact of music on these factors is. SUMMARY BACKGROUND DATA Based on a recently published pilot study on surgical experts, we designed an experiment examining the effects of auditory stress, mental stress, and music on surgical performance and learning, and then correlated the data psychometric measures to the role of music in a novice surgeon’s l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 21 publications
0
42
0
1
Order By: Relevance
“…needed for attention (Table 3). Just as the field studies had shown auditory distractions to be much more prevalent and impactful than visual distractions, in experimental studies the introduction of auditory distractors have been much more common, appearing in 9 of the present studies [8, 2733, 35]. For instance, Feuerbacher et al [35] introduced sounds such as noise from a dropped metal tray, while Moorthy et al [31], Siu et al [29], and Suh et al [8] introduced prerecorded OR noise (at 80–85dB in the first two studies and 50–90dB in the latter two studies).…”
Section: Outcomes Of Distractions On Performancementioning
confidence: 90%
See 3 more Smart Citations
“…needed for attention (Table 3). Just as the field studies had shown auditory distractions to be much more prevalent and impactful than visual distractions, in experimental studies the introduction of auditory distractors have been much more common, appearing in 9 of the present studies [8, 2733, 35]. For instance, Feuerbacher et al [35] introduced sounds such as noise from a dropped metal tray, while Moorthy et al [31], Siu et al [29], and Suh et al [8] introduced prerecorded OR noise (at 80–85dB in the first two studies and 50–90dB in the latter two studies).…”
Section: Outcomes Of Distractions On Performancementioning
confidence: 90%
“…This yielded a total of 102 empirical papers – eleven (11) papers presented findings from observations of distractions in the operating room or from laboratory studies of the effect of distractions on surgical performance [3, 8, 10, 14, 2426, 28, 3335]. A follow-up search replaced “distraction” with “noise” which yielded 752 empirical papers for review – in total five (5) of which were new and topically appropriate [27, 2932].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[281][282][283][284][285] In addition, effective leadership is associated with improvements in staff and patient safety and can mitigate employee work stress and increase job satisfaction. 283,[285][286][287] This has crucial implications in the context of HQHVSN programs because employee stress and work dissatisfaction are known risk factors for musculoskeletal pain [288][289][290][291] and decreased surgical performance 292,293 as well as for depression and suicidal ideation among veterinarians. 294 Leadership skills can be taught, and leadership training is an effective intervention that should be considered for anyone entering a leadership position.…”
Section: Leadershipmentioning
confidence: 99%